Facilitation of evidence implementation within a clinical fellowship program: a mixed methods study. Issue 2 (4th June 2021) - Lizarondo, Lucylynn; McArthur, Alexa; Lockwood, Craig; Munn, Zachary
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background and aim: Facilitation is a multifaceted process for supporting and enabling individual or group of health practitioners to implement positive changes in clinical practice. Facilitation has never been explored within the context of an educational program that integrates a practical, evidence-based implementation component, such as a clinical fellowship program (CFP). The aim of this research was to identify features of facilitation as it occurs in the JBI (formerly known as Joanna Briggs Institute) CFP that promotes the use of evidence into clinical practice. Methods: We used a mixed methods study design to address the objective of this study. An electronic survey was administered to clinicians of different clinical backgrounds who completed the CFP (i.e. clinical fellows). Purposively selected clinical fellows and assigned internal or external facilitators were interviewed. Results: Forty-three clinical fellows completed the survey and 16 individual interviews and two focus groups were conducted. Findings from the survey and interviews demonstrated that facilitation within the context of a CFP is a collaborative effort between assigned facilitators and clinical fellows. Our study showed that both assigned facilitators and clinical fellows perform facilitation activities, with assigned internal and external facilitators providing support and assistance to clinical fellows, who in turn, support the evidence implementation project within their local organization. The study also suggests that external facilitation should be tailored to the individual clinical fellow's characteristics and their previous experiences. Conclusion: Facilitation in an evidence-based CFP involves a partnership between clinical fellows and assigned facilitators, indicating a collaborative effort that involves a set of internal and external facilitation activities. Our study findings can guide the delivery of CFPs, particularly in identifying suitable people for the facilitator's role, which can have important implications for evidence implementation. Future research should focus on evaluating the effectiveness of these programs in improving practice and health outcomes.